In silico evaluation of N-aryl-1,10-phenanthroline-2-amines as potential inhibitors of T. cruzi GP63 zinc-metalloprotease by docking and molecular dynamics simulations - Priscila Goes Camargo; Ramon Borges da Silva; Aline Araujo Zuma; Simon J. Garden; Magaly Girão Albuquerque; Carlos Rangel Rodrigues; Camilo Henrique da Silva Lima (Scientific Reports)
Abstract Based on the in vitro trypanocidal efficacy of previously synthesized N-aryl-1,10-phenanthroline-2-amines (Phen1-20) (aryl = R-phenyl, 1- or 2-naphthyl), we explored the potential interactions of these derivatives as ligands of our comparative model of T. cruzi GP63 (TcGP63). This surface metalloprotease plays a crucial role in parasite adhesion to host cells and aids in cell invasion during T. cruzi infection in Chagas disease. Ligand-protein consensus docking simulations using four GOLD scoring functions revealed that N-(R-phenyl) derivatives (R = CH3, OCH3, CF3, CN, NO2, F, Cl, and Br) presented poses with higher fitness scores than the N-naphthyl ones, with the six para-substituted derivatives (Phen4, p-CH3; Phen7, p-OCH3; Phen10, p-CN; Phen14, p-F; Phen17, p-Cl; and Phen18, p-Br) being more favorable than the ortho or meta ones. Subsequent aqueous molecular dynamics simulation (GROMACS package, CHARMM36 force field, and TIP3P water model) of the ligand-protein complexes for these six top-ranking compounds showed persistent interactions within the TcGP63 active site, primarily through coordination with Zn(II)-cofactor, and H-bonding with catalytic Glu221 and zinc-binding His224. RMSD and RMSF analyses confirmed the stability of these interactions, particularly for compounds with electron-withdrawing groups by inductive effect as R-substituents, such as p-OCH3 (Phen7) and p-CN (Phen10). Binding free energy calculations by the linear interaction energy (LIE) approach corroborated the favorable interactions observed in simulations, highlighting Phen7 and Phen10 as the most promising candidates. This study underscores the potential of N-phenyl-1,10-phenanthroline-2-amines as putative inhibitors targeting the T. cruzi GP63 enzyme.